IN SILICO STUDIES FOR ANTI-BREAST CANCER ACMELLA OLERACEA (L.) FLOWERS - Amrilah, Muhammad Shofi; Hilman, Rifqi (Jurnal Farmasi Sains dan Praktis, 2024)
The study of the efficacy of Acmella oleracea (L.) flowers on breast cancer is still in its early stages. The molecular interaction mechanisms underlying Acmella oleracea's anti-breast cancer activity will be elucidated using in-silico analysis. For this study, seventeen bioactive compounds were used: spilanthol, alpha- and beta-amyrin ester, stigmasterol, beta-sitosterol, alpha-1-sitosterol, 3-acetylaleuritic acid, scopoletin, vanillic acid, trans-ferulic, (72,9E)-2-oxo-undeca-7,9-dienyl 3-methylbut-2-enoate, beta-caryophyllene, beta-pinene, myrcene, caryophyllene oxide, and limone Canonical smiles were obtained from PubChem and inserted into the PASS server to determine biological activity. Several compounds were docked with protein targets, such as ESR1, MAP2K2, and PGR. We used Pyrx 0.8 software for anchoring molecular interaction and Discovery Studio software to visualize the complex binding. In terms of Antineoplastic, apoptosis agonist, caspase-3, caspase-8 stimulant, ovulation inhibitor, steroid synthesis inhibitor, and TP53 expression enhancer, all the compounds tested positive for anticancer activity. According to Swiss ADME and protox analysis, Acmella oleracea flowers have the potential to modulate apoptosis and cell growth. More research is required to confirm the role of Acmella oleracea bioactive compounds in developing target cancers. The study reveals that Acmella oleracea has numerous bioactive chemicals advantageous for cancer therapy by inducing apoptosis through interaction with ESR1, MAPK2, and PGR protein.